PENGARUH KUIS INTERAKTIF BERBASIS DIGITAL (WORDWALL) TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI PERKALIAN PECAHAN DENGAN BILANGAN ASLI SISWA KELAS VI SDI MADAWAT - Nur Ainun; Frederiksen Novenrius Sini Timba; Sonya Kristiani Maria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of digital-based interactive quizzes (Wordwall) on mathematics learning outcomes in the material of fraction multiplication with natural numbers for sixth-grade students at SDI Madawat. This research is motivated by the low mathematics learning outcomes of students caused by conventional and less engaging learning methods. The research method used is a quantitative method with a pre-experimental design using a one-group pretest-posttest design. The research sample consists of 23 sixth-grade students at SDI Madawat, comprising 10 male students and 13 female students. Data collection techniques use tests and observations with instruments in the form of test questions and observation sheets. Data analysis uses the Shapiro-Wilk normality test and paired samples t-test with the assistance of SPSS 27. The results show an increase in students' average scores from 50.43 in the pretest to 80.87 in the posttest. The hypothesis test results show a t-value of 12.0 with a significance of 0.000 (p < 0.05), which means there is a significant effect. Classical completeness in the attitude aspect increased from 43.47% to 95.65%, while in the skills aspect it increased from 34.78% to 91.3%. It can be concluded that the use of Wordwall digital-based interactive quizzes has a significant and effective effect in improving the mathematics learning outcomes of sixth-grade students at SDI Madawat in the material of fraction multiplication with natural numbers.